Formulating Tracing and Linking Algorithm For Identifying Cyber Terrorism Website - Wan Ahmad Ramzi W.Y; Aznizah Ab.Karim; Mohamad Shaufi Kambaruddin; Afzanizam Alias; Mohd Faizal Yahaya (International Journal of Mechanical, Electrical and Civil Engineering, 2025)
Nowadays, the number of cyber terrorists that using Internet as a medium keep increasing around the world are really worrying. Even though the cyber terrorist is publishing their post openly and public, there are quite difficult to recognize their main communication media. This happen because the cyber terrorist might hide their agenda through any sympathetic base website. Therefore, the aim of this project is to formulate tracing and linking algorithm using data mining technique in order to identify the relationship between each cyber terrorism components that may result to cyber terrorism website.